2D / 3D heterojunction layer, preparation method and large-area direct perovskite wafer X-ray detector
By using a 2D/3D heterojunction layer in the perovskite X-ray detector, bismuth iodide is combined with perovskite material, the problem of poor working stability of the detector under long-term irradiation is solved, and higher detection performance and stability are achieved.
Patent Information
- Application Number
- CN202411812503.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Perovskite X-ray detectors have poor operating stability under long-term irradiation or high external bias voltage, resulting in signal distortion and incorrect decision-making.
Using a 2D/3D heterojunction layer, a heterojunction layer is formed by combining bismuth iodide (BiI3) with perovskite material. The high resistivity of bismuth iodide and the high charge mobility of perovskite are used to suppress ion migration and improve carrier transport efficiency.
It significantly improves the operating stability and detection performance of the perovskite X-ray detector, extends the radiation life of the detector, and reduces noise and baseline drift.
Smart Images

Figure CN119653969A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a 2D / 3D heterojunction layer, a preparation method and a large-area direct perovskite wafer X-ray detector, belonging to the technical field of perovskite radiation detection. Background Art
[0002] Perovskite wafer X-ray detectors have attracted much attention as emerging X-ray detectors due to their low cost, controllable thickness, and scalable mass production technology. Considering the actual application scenarios, when the detector device is subjected to continuous irradiation or high external bias during the entire operation period, working stability remains an important issue and has become an important evaluation indicator for the commercialization of this new polycrystalline perovskite detection technology.
[0003] In terms of improving the working stability of polycrystalline X-ray detectors, most of the existing technical solutions are dedicated to improving the characteristics of perovskite itself. At present, the stability of perovskite wafer detectors is mainly maintained by the following measures: (1) Optimizing crystal quality and reducing defect density. Chemical treatment of raw material powder or heat treatment of wafers can promote grain growth and form large and dense grains under pressure, thereby reducing the defect density caused by grain boundaries. Ultimately, the perovskite wafer is made dense and compact, achieving a high migration life product and enhancing the working stability of the detector. (Reference: PbI2-DMSO assisted insitu growth of perovskite wafers for sensitive direct X-ray detection). (2) Using interactions to fix ions, such as enhancing the binding energy with halide ions or the strength of hydrogen bonds. Introducing methyl groups into perovskite to adjust the tolerance factor and enhance hydrogen bonding, inhibiting ion migration and optimizing structural stiffness, ultimately making it show significant stability in long-term temperature aging (-40 to 85°C) (Reference: Metal-free PAZE-NH4X3·H2O perovskite for flexible transparent X-ray detection and imaging). (3) Constructing a hybrid heterostructure. Introducing passivation materials into perovskite wafers to weaken polycrystalline defects and inhibit ion migration. Ultimately, the detector achieves small baseline drift and low noise, significantly improving the radiation stability of the device (Reference: Heteroepitaxial passivation of Cs2AgBiBr6 wafers with suppressed ionic migration for X-ray imaging). (4) Constructing a layered heterostructure. In a porous polymer film, various hybrid 2D perovskite types are combined with 3D perovskites into a stable network to establish a layered heterojunction, achieving a complex balance between spontaneous charge separation / transport, X-ray attenuation and mechanical durability, ultimately enabling thick-film X-ray detectors with high performance, flexible self-driven X-ray detection and imaging capabilities (Reference: Flexible large-scale self-driven perovskite X-ray detector by precise heterogeneous integration). However, the presence of organic cations in hybrid perovskites hinders the transport of photogenerated carriers to a certain extent, which is not conducive to the performance of the detector.
[0004] In addition to improving the crystal quality of the perovskite active layer, the ion migration problem caused by the weak ionic bonds in the inherent halide perovskite still needs to be considered in terms of the working stability of the entire polycrystalline wafer device. For perovskite detector devices that work for a long time in the outer space environment, this inherent source of instability will eventually cause distortion of the recorded signal and ultimately lead to wrong decision-making. Therefore, in terms of maintaining stability, it is necessary to select stable perovskite materials and adopt appropriate strategies to allow carrier (electron or hole) transmission while limiting the passage of other types of ions, thereby achieving the suppression of ion migration. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a 2D / 3D heterojunction layer, a preparation method and a large-area direct-type perovskite wafer X-ray detector.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows.
[0007] A 2D / 3D heterojunction layer comprises a two-dimensional material and a perovskite material, wherein the two-dimensional material is bismuth iodide (BiI3), and the two-dimensional material is used as a heterogeneous layer of a perovskite light absorption layer; the perovskite material is an A2M(I)M(III)X6 type compound, with an energy band of 2 to 2.5 eV, M(I) being a positive monovalent metal ion, and M(III) being a positive trivalent metal ion; the mass ratio of bismuth iodide (BiI3) to the perovskite material is 0.5 to 3:9; using Cu target Kα diffraction, the X-ray powder diffraction pattern of bismuth iodide expressed in 2θ angles has strong diffraction peaks at 27.00°, 35.28°, and 46.22°, and weak diffraction peaks at 12.85°, 25.81°, and 39.12°.
[0008] Preferably, the thickness of the bismuth iodide (BiI3) is 80-120 μm, and the thickness of the perovskite light absorption layer is 800-1200 μm.
[0009] Preferably, the mass ratio of the bismuth iodide (BiI3) to the perovskite material is 1 to 2:9.
[0010] Preferably, the perovskite material is an A2M(I)M(III)X6 type compound, wherein the A-position cation is CH3NH3 + 、NH2-CH=NH2 + , Cs + 、C4H9NH3 + 、CH6N3 + , Rb + and K + One of the following; M(I) is Cu + or Ag + , M(III) is Bi3+ or Sb 3+ ; X is Cl - Br - or I - .
[0011] A method for preparing a 2D / 3D heterojunction layer according to the present invention, the method steps comprising:
[0012] Add AX, M(I)X and M(III)X3 to hydrobromic acid (HBr) according to the stoichiometric ratio, stir and seal, then heat to 90-120°C until the powder is completely dissolved, reduce the temperature by 10-15°C at a rate of 1-3°C / min, then continue to reduce the temperature by 2-5°C at a rate of 0.02-0.06°C / min until nucleation occurs on the liquid surface, keep the temperature for 2-4h, then reduce the temperature to room temperature at a rate of 0.5-1°C / min, filter and wash to obtain perovskite crystals;
[0013] The perovskite crystal is ground, and the obtained perovskite powder is placed in a mold, which is pressed at 10 to 20 MPa for 5 to 10 minutes to obtain a perovskite wafer. The mold is opened, and the fully ground bismuth iodide (BiI3) powder is spread on the surface of the perovskite wafer, and then pressed at 10 to 20 MPa for 2 to 4 hours. After the pressing is completed, the wafer is taken out and annealed on a hot stage at 100 to 200°C for 2 to 4 hours to obtain a 2D / 3D heterojunction layer.
[0014] Preferably, the particle size of the bismuth iodide (BiI3) powder is 1 to 2 μm.
[0015] Preferably, the purity of the bismuth iodide (BiI3) is above 98.0%.
[0016] A large-area direct perovskite wafer X-ray detector comprises a 2D / 3D heterojunction layer according to the present invention, with a thickness of 0.9 to 1.2 mm.
[0017] Preferably, the large-area direct perovskite wafer X-ray detector comprises a metal electrode layer, a 2D / 3D heterojunction layer and a metal electrode layer arranged in sequence from bottom to top.
[0018] Preferably, the metal electrode layer is a carbon electrode, gold, copper, silver, aluminum, chromium or an alloy containing the above metals, and the thickness of the electrode layer is 80 to 500 nm.
[0019] Beneficial Effects
[0020] The present invention provides an application of an inorganic two-dimensional material. Bismuth iodide (BiI3) is combined with perovskite to construct a 2D / 3D heterojunction. The two-dimensional material is added as a heterogeneous layer on the perovskite light absorption layer, and then used in a large-area direct perovskite wafer X-ray detector. After the two-dimensional material is driven by dynamic pressure, its two-dimensional surface gradually becomes perpendicular to the direction of force, so its orientation tends to be consistent, that is, the orientation of the single crystal, resulting in the electrical anisotropy of the layer, providing a potential barrier to hinder ion migration. After forming a heterostructure that meets energy level matching, it is helpful to separate and collect charges, thereby improving the detection performance of X-rays. At the same time, further adjusting the appropriate thickness of bismuth iodide can provide the best carrier transmission distance and the number of photogenerated carriers, thereby achieving the maximum sensitivity effect.
[0021] The present invention provides a 2D / 3D heterojunction layer, which combines bismuth iodide (BiI3) with high resistivity and perovskite material with high charge mobility, solves the ion migration in the perovskite crystal, and is expected to solve the problem of poor working stability in lead-free perovskite devices. At the same time, it is proposed that the inorganic layered 2D / 3D heterostructure may have more advantages in balancing sensitivity and stability.
[0022] The present invention provides a large-area direct-type perovskite wafer X-ray detector. The device constructed by a 2D / 3D heterostructure has good working stability, opens up a new way to simultaneously improve X-ray detection performance and detector stability, and contributes to the research and development of low-cost and high-resolution large-area X-ray imaging equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The XRD diagrams of Experimental Example 1 and Comparative Example 3 are shown in FIG.
[0024] Figure 2 This is a high-resolution FE-SEM image of the cross section of Experimental Example 1.
[0025] Figure 3 Statistical graph of X-ray sensitivity of devices made in Experimental Examples 1-3 and Comparative Example 4.
[0026] Figure 4 Statistical graph of X-ray sensitivity of devices made in Experimental Example 1 and Comparative Examples 1-4.
[0027] Figure 5 Detection limit diagram of the devices of Experimental Example 1 and Comparative Example 4.
[0028] Figure 6 This is a diagram of the radiation working stability of the device made in Experimental Example 1. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below in conjunction with specific embodiments.
[0030] A method for preparing a large-area direct perovskite wafer X-ray detector, the method steps are as follows:
[0031] Step 1: Weigh the perovskite crystal and grind it thoroughly to obtain a uniform powder, then put the powder into a circular mold and apply vertical pressure to the mold with a hydraulic press for two hours. The thickness of the wafer can be controlled by adjusting the amount of powder and the pressure applied.
[0032] Step 2: Open the upper part of the mold and spread bismuth iodide (BiI3) powder on the top of the perovskite;
[0033] Step 3: After reloading the upper mold, press at 10 MPa for two hours;
[0034] Step 4: After taking out the wafer, anneal it on a hot plate at 100°C for two hours;
[0035] Step 5: Under high vacuum conditions, evaporate an electron transport layer on the perovskite light absorption layer; under high vacuum conditions, evaporate a metal layer on the heterogeneous crystalline sheet to prepare a large-area direct perovskite chip X-ray detector.
[0036] Experimental Example 1
[0037] Step 1: Place 0.426g of cesium bromide (CsBr), 0.449g of bismuth bromide (BiBr3) and 0.188g of silver bromide AgBr in a glass bottle, add 12.5ml of hydrobromic acid (HBr), and stir appropriately. Seal the glass bottle with 3M tape, place it in an oil bath and heat it to 95°C until the powder is completely dissolved to form a light yellow solution. Reduce the oil bath temperature to 85°C at a rate of 3°C / h, and then continue to cool to 82°C at a rate of 0.05°C / h until nucleation occurs on the liquid surface. After nucleation, maintain this temperature for three hours, and then cool it down to room temperature again at a rate of 0.5°C / h. Finally, pour out the residual solution, rinse the crystals with ethanol and isopropanol to obtain Cs2AgBiBr6 crystals.
[0038] Step 2: Weigh 1 g of Cs2AgBiBr6 crystals and grind them thoroughly to obtain uniform Cs2AgBiBr6 powder.
[0039] Step 3: Place the powder into a circular mold and use a hydraulic press to apply a vertical pressure of 10 MPa to the mold (equivalent to the powder being subjected to a pressure of 187 MPa) and maintain it for two hours.
[0040] Step 4: Open the upper part of the mold and spread 0.2g of ground BiI3 powder on top of Cs2AgBiBr6. After reloading the upper part of the mold, press at 10MPa for two hours.
[0041] Step 5: After taking out the heterogeneous crystal sheet, annealing treatment is performed on a hot stage at 100°C for two hours.
[0042] Step 6: Transfer the sample obtained in step 5 to a high vacuum evaporator, evaporate 50nm Au electrodes on both sides, and finally obtain a large-area chip X-ray detector.
[0043] Experimental Example 2
[0044] The same preparation process as in Experimental Example 1 was used, except that in step 4, 0.4 g of ground BiI3 powder was added, and other conditions remained the same.
[0045] Experimental Example 3
[0046] The same preparation process as in Experimental Example 1 was used, except that in step 4, 0.6 g of ground BiI3 powder was added, and other conditions remained the same.
[0047] Comparative Example 1
[0048] Step 1: Dissolve 4-fluorophenethylammonium iodide (F-PEAI) and BiI3 in hydroiodic acid (HI) at a molar ratio of 3:1. Then, stir at 110°C for several hours and immediately filter with a 0.45 μm PTFE filter. Cool the solution at a rate of 2°C / h to obtain (F-PEA)3BiI6 crystals.
[0049] Step 2: Grind (F-PEA)3BiI6 crystals and Cs2AgBiBr6 crystals into powders respectively.
[0050] Step 3: After 1g of Cs2AgBiBr6 powder was placed in the mold and pressed, the upper part of the mold was opened and 0.2g of (F-PEA)3BiI6 powder was spread on top of the Cs2AgBiBr6. After the upper mold was reloaded, the pressing was carried out at 10MPa for two hours.
[0051] Step 4: After taking out the wafer, annealing treatment is performed on a hot stage at 100°C for two hours.
[0052] Step 5: Transfer the sample obtained in step 4 to a high vacuum evaporator, evaporate 50nm Au electrodes on both sides, and finally obtain a large-area chip X-ray detector.
[0053] Comparative Example 2
[0054] The same preparation process as in Experimental Example 1 was used, except that in steps 3 and 4, Cs2AgBiBr6 and BiI3 powders were mixed at a mass ratio of 9:1 and then pressed. Other conditions remained the same.
[0055] Comparative Example 3
[0056] The same preparation process as in Experimental Example 1 was used, except that only BiI3 powder was used for pressing in steps 3 and 4. Other conditions remained the same.
[0057] Comparative Example 4
[0058] The same preparation process as in Experimental Example 1 was adopted, except that in step 4, BiI3 powder was not added, and other conditions remained the same.
[0059] Performance Testing:
[0060] (1) X-ray diffraction (XRD): Testing equipment: Bruker D8-DISCOVER X-ray diffractometer; Testing conditions: room temperature, wafer sample.
[0061] Test results: Figure 1 The XRD characterization results of BiI3 in the perovskite wafers of Experimental Example 1 and Comparative Example 3 are shown. Compared with the BiI3 powder, the XRD spectrum of the BiI3 side of the heterogeneous wafer shows a huge change in the relative intensity of the diffraction peaks similar to that of the pure BiI3 wafer, indicating that when the BiI3 powder is subjected to vertical orientation pressure in a limited space, its crystal orientation tends to be consistent with that of the BiI3 single crystal.
[0062] (2) Field emission scanning electron microscope (FE-SEM): Test equipment: Gemini 300; Test conditions: room temperature, wafer sample.
[0063] Test results: Figure 2 The high-resolution FE-SEM image results of the cross section of the heterogeneous crystal sheet in Experimental Example 1. The thickness of the BiI3 layer is 103.9 microns, and the BiI3 powder is in contact with the Cs2AgBiBr6 grains in a flat manner. The clear and smooth interface between the two-dimensional layer and the three-dimensional substrate means that a unidirectional 2D / 3D heterogeneous crystal sheet, i.e., a double-layer structure, is formed, which is conducive to the formation of a built-in electric field to separate electrons and holes.
[0064] (3) X-ray detector sensitivity: Test equipment: X-ray tube (Mini-X2) and Keithley 2636B source meter. Test conditions: Room temperature, wafer X-ray detector.
[0065] Test results: Figure 3The X-ray sensitivity of the samples prepared in Experimental Examples 1-3 and Comparative Example 4 is statistically analyzed by an X-ray test system. In Experimental Example 1, adding 10% BiI3 by total mass makes the heterogeneous wafer show the best sensitivity. In Experimental Examples 2 and 3, adding more BiI3, i.e., thicker BiI3 layers in the heterogeneous crystal sheets show decreased sensitivity. It is difficult for the device made in Comparative Example 4 to obtain high sensitivity under large electric fields. Figure 4 The X-ray sensitivity of the samples prepared in Experimental Example 1 and Comparative Examples 1-4 is statistically analyzed by an X-ray test system. Compared with the devices in the comparative examples, the Cs2AgBiBr6 / BiI3 heterogeneous wafer detector prepared in Experimental Example 1 exhibits the highest sensitivity. The addition of BiI3 provides its own X-ray response and the formation of a built-in electric field, further improving the sensitivity of the wafer detector device.
[0066] (4) X-ray detector detection limit: Test equipment: X-ray tube (Mini-X2) and Keithley 2636B source meter. Test conditions: Room temperature, wafer X-ray detector.
[0067] Test results: Figure 5 is the current density related to the dose rate in the devices of Experimental Example 1 and Comparative Example 4. The detection limit of the heterogeneous wafer device in Experimental Example 1 is one order of magnitude lower than that of the device in Comparative Example 4. BiI3 as a heterogeneous layer provides a barrier to suppress noise and ion migration in the electric field direction, further improving the detection limit of the wafer detector device.
[0068] (5) Stability test: Test equipment: X-ray tube (Mini-X2) and Keithley 2636B source meter. Test conditions: Room temperature, wafer X-ray detector.
[0069] Test results: Figure 6 The photocurrent of the heterogeneous crystal device prepared in Experimental Example 1 under continuous radiation. The heterogeneous wafer X-ray detector has a cumulative dose of up to 4.015Gy air After X-ray irradiation, the response current only decreased by 2.6%. The addition of BiI3 improved the radiation stability. In summary, BiI3 is an excellent inorganic 2D layered material that can be used to improve the sensitivity and stability of perovskite X-ray detectors, which can be extended to other heterojunction systems and achieve expected results.
[0070] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A 2D / 3D heterojunction layer, characterized in that: It includes a two-dimensional material and a perovskite material, wherein the two-dimensional material is BiI3, and the BiI3 is used as a heterogeneous layer of a perovskite light absorption layer; the perovskite material is an A2M(I)M(III)X6 type compound, with an energy band of 2 to 2.5 eV, M(I) being a positive monovalent metal ion, and M(III) being a positive trivalent metal ion; the mass ratio of BiI3 to the perovskite material is 0.5 to 3:9; using Cu target Kα diffraction, the X-ray powder diffraction spectrum of BiI3 expressed at a 2θ angle has strong diffraction peaks at 27.00°, 35.28°, and 46.22°, and weak diffraction peaks at 12.85°, 25.81°, and 39.12°.
2. A 2D / 3D heterojunction layer according to claim 1, characterized in that: The thickness of the BiI3 is 80-120 μm, and the thickness of the perovskite light absorption layer is 800-1200 μm.
3. The 2D / 3D heterojunction layer according to claim 1, characterized in that: The mass ratio of BiI3 to perovskite material is 1 to 2:
9.
4. A 2D / 3D heterojunction layer according to claim 1, 2 or 3, characterized in that: The perovskite material is an A2M(I)M(III)X6 type compound, wherein the A-position cation is CH3NH3 + 、NH2-CH=NH2 + , Cs + 、C4H9NH3 + 、CH6N3 + , Rb + and K + One of them; M(I) is Cu + or Ag + , M(III) is Bi 3+ or Sb 3+ ; X is Cl - Br - or I - .
5. A method for preparing a 2D / 3D heterojunction layer according to any one of claims 1 to 4, characterized in that: The method steps include: Add AX, M(I)X and M(III)X3 to hydrobromic acid according to the stoichiometric ratio, stir and seal, then heat to 90-120°C until the powder is completely dissolved, reduce the temperature by 10-15°C at a rate of 1-3°C / min, then continue to reduce the temperature by 2-5°C at a rate of 0.02-0.06°C / min until nucleation occurs on the liquid surface, keep the temperature for 2-4h, then reduce the temperature to room temperature at a rate of 0.5-1°C / min, filter and wash to obtain perovskite crystals; The perovskite crystal is ground, and the obtained perovskite powder is placed in a mold, which is pressed at 10-20 MPa for 5-10 minutes to obtain a perovskite wafer. The mold is opened, and the fully ground BiI3 powder is spread on the surface of the perovskite wafer, which is then pressed at 10-20 MPa for 2-4 hours. After the pressing is completed, the wafer is taken out and annealed on a hot stage at 100-200°C for 2-4 hours to obtain a 2D / 3D heterojunction layer.
6. A method for preparing a 2D / 3D heterojunction layer according to claim 5, characterized in that: The particle size of the BiI3 powder is 1-2 μm.
7. The method for preparing a 2D / 3D heterojunction layer according to claim 5, characterized in that: The purity of BiI3 is above 98.0%.
8. A large-area direct perovskite wafer X-ray detector, characterized in that: A 2D / 3D heterojunction layer comprising any one of claims 1 to 4, having a thickness of 0.9 to 1.2 mm.
9. A large-area direct perovskite wafer X-ray detector as claimed in claim 8, characterized in that: The large-area direct perovskite wafer X-ray detector comprises a metal electrode layer, a 2D / 3D heterojunction layer and a metal electrode layer which are sequentially arranged from bottom to top.
10. A large-area direct perovskite wafer X-ray detector as claimed in claim 9, characterized in that: The metal electrode layer is a carbon electrode, gold, copper, silver, aluminum, chromium or an alloy containing the above metals, and the thickness of the electrode layer is 80-500nm.
Citation Information
Patent Citations
Bismuth iodide two-dimensional material and preparation and application thereof
CN107093560A
Tin (II)-based perovskite mixture heterojunction thin film, preparation method and photoelectric detector
CN115996582A
Perovskite heterojunction for direct X-ray detector and construction method thereof
CN116634826A
Multi-step tableting perovskite heterogeneous crystal circular X-ray detector and preparation method thereof
CN117651465A